Hierarchical mesoporous titania nanoshell encapsulated on polyimide nanofiber as flexible, highly reactive, energy saving and recyclable photocatalyst for water purification. (20th April 2020) - Dong, Guoqing; Wang, Yanan; Lei, Huanyu; Tian, Guofeng; Qi, Shengli; Wu, Dezhen
Abstract: Titania is well known for its outstanding photocatalytic performance and widely applied in contaminants removal, air purification and water disinfection. However, directly using of titania powders in these applications will bring several drawbacks, such as low light utilization, costly separation recovery and human health concerns. Hence, numerous efforts have been tried for immobilization of titania on various substrates in order to overcome the aforementioned issues. Moreover, traditional methods for immobilization of titania on polymer substrates also have the disadvantages of surface area reduction, titania leaching and polymer degradation by oxidative radicals. Thus, in this work, a novel hierarchical mesoporous titania nanoshell@polyimide nanofiber is constructed via the in-situ complexation-hydrolysis strategy by utilizing titanium oxysulfate as the precursor of titania and sulfuric acid as the crystal structure regulator. Benefited from the hierarchical mesoporous titania nanoshell and ultrafine electrospun polyimide nanofiber, a superior high reactive surface area is achieved (213 m 2 /g) via the stacking of nanopores (pore size distribution: 2–4 nm, 41.4%; 4–10 nm, 36.7%; 10–20 nm, 21.9%), leading to the excellent photocatalytic activity. Additionally, this buoyant PI nanofiber supported photocatalyst exhibits superb flexibility, and is highly reactive and energy saving since it can be easily recovered from the contaminated water without costly separation compared to the traditional titania slurry. More importantly, this unique photocatalyst demonstrates admirable photocatalytic efficiency retention (88%) after 10 cycles, which makes it a recyclable and economical photocatalytic material. Graphical abstract: A novel hierarchical mesoporous titania nanoshell@polyimide nanofiber is constructed via the in-situ complexation-hydrolysis strategy. This unique core-shell hybrid nanofiber manifests super high reactive surface area (213 m 2 /g), smaller pore size (2.7 nm), great photocatalytic activity and admirable photocatalytic efficiency retention (88%) after 10 cycles, which makes it a flexible, energy saving and recyclable photocatalyst. Image 1 Highlights: A novel hierarchical mesoporous TiO2 nanoshell@polyimide nanofiber is constructed. Superior high reactive surface area is achieved from hierarchical mesoporous TiO2 nanoshell and ultrafine PI nanofiber. The PI nanofiber supported photocatalyst exhibits superb flexibility, reactivity, energy saving and recyclability.